ADMINISTRASI PENDIDIKAN MASA PANDEMI - Muhammad ‘Aqdil Afdhali (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
Teaching services will run when supported by the availability of teachers who are proportional to the number of students. Teaching services that began with an online form for three months did not run well due to internet facilities, cellphones and the presence of students who had not been able to make adjustments. Due to this obstacle, an evaluation process was carried out and an anticipatory measure was carried out by changing the teaching pattern from online to face-to-face limited in groups with the permission of the village government. Through this teaching service process, it can be seen that public service actions carried out during the Covid 19 pandemic must continue to be evaluated so that the objectives of service delivery can be achieved through appropriate policy measures. Teaching facility services that occur to support the teaching and learning process are fulfilled by collaboration between schools, village governments and parents. The meaning that can be taken from the process of public administration in the service of teaching facilities is that to realize quality public services, every public organization cannot run alone but requires collaborative management with other parties including parents and village governments.